2020
DOI: 10.1002/aorn.12991
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines in Practice: Surgical Attire

Abstract: Surgical attire provides a barrier to microorganisms shed from health care workers’ skin and hair to help protect patients and promote a clean environment. The AORN “Guideline for surgical attire” includes recommendations for selecting, wearing, and cleaning surgical attire that are based on the highest‐quality evidence available. Recommendations are rated as Regulatory Requirement, Recommendation, Conditional Recommendation, or No Recommendation according to the level of evidence, an assessment of the benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Hence, it is advisable to put this educational intervention into practice within operating theatres. However, when implementing the educational intervention, the latest AORN 2020 guidelines on the use of surgical attire should be used (Link 2020 ), as this version was not yet published when the pilot study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is advisable to put this educational intervention into practice within operating theatres. However, when implementing the educational intervention, the latest AORN 2020 guidelines on the use of surgical attire should be used (Link 2020 ), as this version was not yet published when the pilot study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory bodies have suggested that OR personnel cover their arms with surgical jackets and wear a "clean surgical head cover or hood that confines all hair and completely covers the ears, scalp skin, sideburns, and nape of the neck." 8 Although not explicitly stated, this has been understood by many institutions as a recommendation for bouffants and against surgical caps in an effort to decrease the risk of SSIs. 8 Our data add support to the growing body of literature suggesting that these wellintentioned regulations have not been shown to have an effect on SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although not explicitly stated, this has been understood by many institutions as a recommendation for bouffants and against surgical caps in an effort to decrease the risk of SSIs. 8 Our data add support to the growing body of literature suggesting that these wellintentioned regulations have not been shown to have an effect on SSIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations